2018
DOI: 10.1038/s41467-018-05208-2
|View full text |Cite
|
Sign up to set email alerts
|

Nucleoporin 107, 62 and 153 mediate Kcnq1ot1 imprinted domain regulation in extraembryonic endoderm stem cells

Abstract: Genomic imprinting is a phenomenon that restricts transcription to predominantly one parental allele. How this transcriptional duality is regulated is poorly understood. Here we perform an RNA interference screen for epigenetic factors involved in paternal allelic silencing at the Kcnq1ot1 imprinted domain in mouse extraembryonic endoderm stem cells. Multiple factors are identified, including nucleoporin 107 (NUP107). To determine NUP107’s role and specificity in Kcnq1ot1 imprinted domain regulation, we deplet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
38
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 64 publications
9
38
2
Order By: Relevance
“…5 Here, we hypothesized that NUP107, NUP62 and NUP153, but not NUP98, play a regulatory role at the Kcnq1ot1 imprinted domain in ES and TS cells, and may contribute to the differential regulation of the Kcnq1ot1 imprinted domain between ES, TS and XEN cells. In the current study, we identified a conserved mechanism of nucleoporin regulation of the Kcnq1ot1 imprinted domain in ES and TS cells, as previously identified in XEN cells (Sachani et al, 2018). NUP107, NUP62 and NUP153 bind to the Kcnq1ot1 ICR on each side of the Kcnq1ot1 ncRNA promoter, and are required for paternal Kcnq1ot1 ncRNA expression, positioning of the paternal Kcnq1ot1 domain at the nuclear periphery, as well as recruitment of histone modifiers at the paternal Kcnq1ot1 ICR in both ES and TS cells.…”
supporting
confidence: 54%
See 4 more Smart Citations
“…5 Here, we hypothesized that NUP107, NUP62 and NUP153, but not NUP98, play a regulatory role at the Kcnq1ot1 imprinted domain in ES and TS cells, and may contribute to the differential regulation of the Kcnq1ot1 imprinted domain between ES, TS and XEN cells. In the current study, we identified a conserved mechanism of nucleoporin regulation of the Kcnq1ot1 imprinted domain in ES and TS cells, as previously identified in XEN cells (Sachani et al, 2018). NUP107, NUP62 and NUP153 bind to the Kcnq1ot1 ICR on each side of the Kcnq1ot1 ncRNA promoter, and are required for paternal Kcnq1ot1 ncRNA expression, positioning of the paternal Kcnq1ot1 domain at the nuclear periphery, as well as recruitment of histone modifiers at the paternal Kcnq1ot1 ICR in both ES and TS cells.…”
supporting
confidence: 54%
“…Previous studies have identified roles for nucleoporins in gene regulation in yeast, Drosophila, and mammalian cells, although the mechanisms by which nucleoporins govern this regulation is not fully understood (Capelson et al, 2010;Jacinto et al, 2015; Kalverda et al, 2010; Light et al, 2013; Mendjan et al, 2006; Vaquerizas et al, 2010). Our investigation of nucleoporins, NUP107, NUP62, and NUP153, revealed a nucleoporin-dependent imprinting regulatory mechanism that mediates Kcnq1ot1 imprinted domain regulation in XEN cells, without impairment of nuclear-cytoplasmic transport function (Sachani et al, 2018). More specifically, our data showed that depletion of Nup107, Nup62 and Nup153 in mouse XEN cells led to a reduction in Kcnq1ot1 noncoding RNA expression and its volume at the paternal Kcnq1ot1 domain; a shift in positioning of paternal Kcnq1ot1 domain away from the nuclear periphery; and reactivation of a subset of normally silent paternal alleles of protein-coding genes in the domain.While DNA methylation at the Kcnq1ot1 ICR was not altered, Nup107, Nup62 and Nup153 depletion altered active and repressive histone modifications and reduced cohesin interactions at the Kcnq1ot1 ICR.…”
mentioning
confidence: 84%
See 3 more Smart Citations